Climate Change Effects on the Major Crops of Bangladesh and the Adaptation Measures- A Review of Literature (SAARC Journal of Agriculture, 2025)
Bangladesh is a vast and resourceful nation, yet natural calamities often afflict it due to climate change (CC). Agriculture is the most vulnerable sector of the Bangladeshi economy due to CC. The North and Northwest areas of Bangladesh are severely impacted by CC-related natural calamities such as drought and high temperatures. The Southern and Southeast coastal areas are especially susceptible to rising sea levels, salt intrusions, and cyclones. Flooding stands as the principal natural disaster wreaking havoc on agriculture throughout Bangladesh, impacting almost every division each year with its devastating effects.  Due to the rising sea levels, the Southern region of Bangladesh would produce 30 percent less Boro rice. Rice output would fall by 28 percent and wheat production by 68 percent if the temperature were to climb. Climate Change would lower the average output of rain-fed maize by 3.3 percent to 6.4 percent by 2030 and by 5.2 percent to 12.0 percent by 2050. Potato yields would likely decrease by 8.7 percent in 2075 because of soil moisture stress. From 2015 to 2020, the Khulna division in Bangladesh faced the most significant crop losses caused by climate-related disasters, while the Chattogram division recorded the least amount of crop damage during the same period. Bangladesh’s most prevalent adaptation systems are agricultural and infrastructural management, whereas farm management is the least prevalent. Irrigation, obtaining loans, using tractors, and pesticides are farmer’s most effective adaptation strategies in Bangladesh.SAARC J. Agric., 23(1): 54-67 (2025)